2018
DOI: 10.1029/2017jf004358
|View full text |Cite
|
Sign up to set email alerts
|

Tidewater Glacier Surges Initiated at the Terminus

Abstract: There have been numerous reports that surges of tidewater glaciers in Svalbard were initiated at the terminus and propagated up-glacier, in contrast with downglacier-propagating surges of land-terminating glaciers. Most of these surges were poorly documented, and the cause of this behavior was unknown. We present detailed data on the recent surges of two tidewater glaciers, Aavatsmarkbreen and Wahlenbergbreen, in Svalbard. High-resolution time series of glacier velocities and evolution of crevasse patterns sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 61 publications
7
66
0
Order By: Relevance
“…When the major collapse initiated in 2014/2015, diffusivity was low (mostly < 1 × 10 5 m 2 /day, Figure 4e) and the perturbation at the thinning center (8-10 km distance from 1984 terminus) was dominated by advection. A similar process has been observed in many tidewater glaciers of Svalbard (e.g., McMillan et al, 2014;Murray et al, 2012;Nuth et al, 2019;Sevestre et al, 2018;. In 2016, the downstream region (0-15 km distance from 1984 terminus) reached a high diffusivity (> 2 × 10 5 m 2 /day) and a low |P e | while the upstream region still underwent advection (P e ≈ −6).…”
Section: Transition From a Collapse To An Ice Streamsupporting
confidence: 70%
See 2 more Smart Citations
“…When the major collapse initiated in 2014/2015, diffusivity was low (mostly < 1 × 10 5 m 2 /day, Figure 4e) and the perturbation at the thinning center (8-10 km distance from 1984 terminus) was dominated by advection. A similar process has been observed in many tidewater glaciers of Svalbard (e.g., McMillan et al, 2014;Murray et al, 2012;Nuth et al, 2019;Sevestre et al, 2018;. In 2016, the downstream region (0-15 km distance from 1984 terminus) reached a high diffusivity (> 2 × 10 5 m 2 /day) and a low |P e | while the upstream region still underwent advection (P e ≈ −6).…”
Section: Transition From a Collapse To An Ice Streamsupporting
confidence: 70%
“…The analysis of P e also shows that once a glacier begins to collapse, P e is likely to decrease, causing thinning or thickening perturbations to diffuse inland (or advect inland if P e is negative enough). A similar process has been observed in many tidewater glaciers of Svalbard (e.g., McMillan et al, 2014;Murray et al, 2012;Nuth et al, 2019;Sevestre et al, 2018;. Fowler and Johnson (1996) point out mathematically that this process can also take place on an ice sheet and subsequently form an ice stream, although an ice sheet surge has never been observed in the modern data records.…”
Section: Transition From a Collapse To An Ice Streamsupporting
confidence: 65%
See 1 more Smart Citation
“…This behaviour has been observed on several marine-terminating glaciers on Svalbard (e.g. Murray and others, 2003;Sevestre and others, 2018), as well as in the Canadian Arctic (Van Wychen and others, 2016), but is rather unlikely to have occurred on GF at the time since the terminus was then grounded well above sea level, behind a ∼1 km wide and 30 m high moraine (Müller, 1969). That being said, it would appear that the ice front reached fjord waters at some time in the mid-1960s, and the terminal moraine became progressively submerged as the terminus advanced past the nunatak and into a wider section of the valley (Fig.…”
Section: A Spectrum Of Flow Instabilitiessupporting
confidence: 68%
“…We suggest that surge conditions were primed by thickening of the ice, increase in slope, and late season high melt in 2001 but that the timing was determined by the large amount of meltwater produced in summer 2002. A study of two tidewater glaciers in Svalbard also concluded that the observed surges were preconditioned by internal mechanisms but set off by external processes (Sevestre et al, ).…”
Section: Discussionmentioning
confidence: 99%